2018
DOI: 10.1038/s41467-018-05774-5
|View full text |Cite
|
Sign up to set email alerts
|

High entropy oxides for reversible energy storage

Abstract: In recent years, the concept of entropy stabilization of crystal structures in oxide systems has led to an increased research activity in the field of “high entropy oxides”. These compounds comprise the incorporation of multiple metal cations into single-phase crystal structures and interactions among the various metal cations leading to interesting novel and unexpected properties. Here, we report on the reversible lithium storage properties of the high entropy oxides, the underlying mechanisms governing these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
705
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 928 publications
(729 citation statements)
references
References 33 publications
19
705
0
5
Order By: Relevance
“…Selected charge/discharge curves and the lithiation capacities achieved over the first 100 cycles are shown in Figure . The results are in good agreement with previously published data . In recent years, it has been shown that the use of FEC instead of EC in LP57 electrolyte is beneficial to the long‐term cycling performance of especially alloying and conversion anode materials.…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…Selected charge/discharge curves and the lithiation capacities achieved over the first 100 cycles are shown in Figure . The results are in good agreement with previously published data . In recent years, it has been shown that the use of FEC instead of EC in LP57 electrolyte is beneficial to the long‐term cycling performance of especially alloying and conversion anode materials.…”
Section: Resultssupporting
confidence: 91%
“…HEO was prepared by the NSP method . Mg(NO 3 ) 2 ⋅ 6H 2 O (Sigma Aldrich, 99.9 %), Zn(NO 3 ) 2 ⋅ 6H 2 O (Alfa Aesar, 99.9 %), Cu(NO 3 ) 2 ⋅ 2.5H 2 O (Sigma Aldrich, 99.9 %), Ni(NO 3 ) 2 ⋅ 6H 2 O (Sigma Aldrich, 99.9 %) and Co(NO 3 ) 2 ⋅ 6H 2 O (Sigma Aldrich, 99.9 %) served as precursors in the synthesis, with the final material forming in the gas phase of a hot‐wall reactor at 1150 °C and subsequent sintering at 1000 °C for 1 h …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations